Translanguaging, Emotionality, and English as a Second Language Immigrants: Mongolian Background Women in Australia - Dovchin, Sender (2021)
Drawing on the translanguaging practices of Mongolian background English as a Second Language (ESL) immigrant women in Australia, this paper points out two main theoretical points: (1) when translanguaging moves beyond the classroom, it may provide ESL immigrants with an emotionally and linguistically safe space where they feel comfortable in managing their negative emotions through employing multiple entangled layers of linguistic and paralinguistic resources; (2) translanguaging data further presents that these ESL immigrants are deeply emotional and are prone to depression, putting their mental well-being in jeopardy. As a result of their depression, their academic concentration is inhibited, as is their ability to learn English well or easily. We, as TESOL educators, therefore, need to consider two critical educational implications: (1) how ESL immigrant students use different linguistic repertoires outside the classroom, what they talk about, and which emotions they prefer to express in which forms of their linguistic repertoire; and their multiple emotions, traumas and psychological issues embedded within their multiple ways of learning, being, and speaking; (2) consolidate appropriate interventions aimed at reducing depressive symptoms that have the potential to negatively impact academic performance existing in L2 sociocultural contexts.